Recovery of nickel from industrial wastewater by homogeneous fluidized-bed granulation (FBG) process - Salcedo, Angel Frances M. (College of Engineering, University of the Philippines Diliman, 2015)
Nickel, commonly known for its anti-corrosion property, is used in various industries such as decorative, engineering and electroforming. The increase in demand and industrial use of nickel, and the improper management of nickel-containing wastewater may potentially contaminate different bodies of water. In turn, this may negatively affect human health and the environment. The removal of nickel from wastewater is one of the industry's primary interests. This study focuses on the recovery of nickel from synthetic electroplating solution using homogeneous fluidized-bed granulation process. Using a laboratory scale fluidized-bed, continuous process was carried out by varying initial nickel concentration (100 ppm, 200 ppm, 300 ppm, 400 ppm), molar ratio [CO3]/[Ni] (0.5, 1.0, 2.0), and pH value (10.5, 10.8, 11.0). Use of Watts bath electroplating wastewater (containing NiCl2.6H2O, NiSO4.6H2O, and H3BO3) and addition of calcium (CaCl2.2H2O, at 20 ppm, 50 ppm and 100 ppm), both varied at different experimental parameters, were also conducted in the study. Different effects driven by supersaturation were investigated to determine the significant importance of each factor in the production of granules and removal of nickel from wastewater. The removal of nickel ranged from 85% to 99%: 91% to 99% when using pure nickel solution; 92% to 97% when using synthetic Watts electroplating bath wastewater, 87% to 93% through the addition of calcium in synthetic wastewater, and 85% when using synthetic wastewater diluted in tap water.